2001
DOI: 10.1021/jp010874n
|View full text |Cite
|
Sign up to set email alerts
|

Lecithin Organogel with New Rheological and Scaling Behavior

Abstract: It was established from an experimental study on a lecithin organogel in n-decane performed by means of an oscillatory rheology that frequency dependencies for complex viscosity and storage modulus have intermediate plateaus at certain molar ratios of water to lecithin. This type of rheological behavior was previously observed for blends of homopolymers which differ significantly in their molecular weight. To mathematically describe the experimental data, a Maxwell model including two relaxation processes (i.e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 27 publications
0
15
1
Order By: Relevance
“…Thus, the bilayer structures lead to the formation of vesicles or liposomes, the size of which is significantly dependent upon the number of factors such as concentration (1,2), temperature (3), ionic strength (3,4), morphological changes, etc. Since the phospholipids with higher fatty acid chains only exist in the form of bilayer structures, they can be studied as the model system for biomembranes (5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the bilayer structures lead to the formation of vesicles or liposomes, the size of which is significantly dependent upon the number of factors such as concentration (1,2), temperature (3), ionic strength (3,4), morphological changes, etc. Since the phospholipids with higher fatty acid chains only exist in the form of bilayer structures, they can be studied as the model system for biomembranes (5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Long tubular micelles of 2.0-2.5 nm radius and hundreds to thousands of nanometers will be formed upon further addition of polar solvent (39,40). Once these micelles attain a critical length, they start to overlap, followed by the intertwining, which results in the formation of a three-dimensional network (29,(41)(42)(43)(44)(45)(46). This offers the system an enhanced viscosity and viscoelastic property, which results in the formation of a jellylike structure.…”
Section: Mechanism Of Organogelationmentioning
confidence: 99%
“…Compatibility studies with human skin revealed that topical use of LOs is safe (Dreher et al 1997 ;Shchipunov et al 2001 ;Schurtenberger et al 1990 ). Vehicles (organic solvents, such as fatty acid esters, e.g., isopropyl myristate, ethyl oleate) used for preparing LOs are also GRAS excipients.…”
Section: Biological Physical and Chemical Safetymentioning
confidence: 99%
“…If polar additive concentration is increased further, fl exible and long tubular micelles from 2.0 to 2.5 nm in radius and nanometer length are formed (Shchipunov and Schmiedel 1996a, b). After reaching a critical length, these extended micelles begin to overlap, entangle themselves, and build up a transient 3-dimensional network (Shchipunov and Hoffmann 2000 ;Voit and Shchipunov 2000 ;Shchipunov et al 2001 ).…”
Section: Mechanism Of Formation Lecithin Organogels (Los)mentioning
confidence: 99%